BEHAVIOR OF PINNED SCROLL WAVES WITH DIFFERENT EXCITABILITY IN A SIMULATED EXCITABLE MEDIA - Wattanasiripong, Nuttapong; Kumchaiseemak, Nakorn; Porjai, Porramain (Progress in Applied Science and Technology, 2018)
The emerging of pinning phenomena is described in many dynamical systems such as superconductivity and super fluidity. The dynamics of pinned scroll waves play an important role in the human health causing longer tachycardia. In this research, we present an investigation the properties parameter (i.e. wave period, wavelength and wave velocity) of pinned scroll waves with different excitability of the media in the two-variable Oregnator model. The cylindrical obstacle is fixed constant. We found both wave period T and wavelength decrease with increasing the excitability. However, the wave velocity increases with excitability.